2020
DOI: 10.5194/amt-2020-64
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrieval of aerosol properties from Airborne Hyper Angular Rainbow Polarimeter (AirHARP) observations during ACEPOL 2017

Abstract: Multi-angle polarimetric (MAP) imaging of Earth scenes can be used for the retrieval of microphysical and optical parameters of aerosols and clouds. The Airborne Hyper-Angular Rainbow Polarimeter (AirHARP) is an aircraft MAP 15 instrument with the hyper-angular imaging capability of 60 along-track viewing angles at 670 nm, and 20 along-track viewing angles at other wavelengths 440, 550, 870 nm across the full 114 ̊ (94 ) along-track (cross-track) field-of-view. Here we report the retrieval of aerosol propertie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These HSRL-2 measurements are used to compute AOD as well as the aerosol extinction / backscatter ratio ("lidar ratio") at 355 and 532 nm. Rogers et al (2009) evaluated the HSRL extinction coefficient profiles and found that the HSRL extinction profiles are within the systematic errors of airborne in situ measurements at visible wavelengths. Derived products include, first, estimates of planetary boundary layer heights which use the vertically resolved profile measurements of aerosol backscatter to derive aerosol mixed-layer heights during the daytime (Scarino et al, 2014).…”
Section: The High Spectral Resolution Lidar (Hsrl-2)mentioning
confidence: 95%
“…These HSRL-2 measurements are used to compute AOD as well as the aerosol extinction / backscatter ratio ("lidar ratio") at 355 and 532 nm. Rogers et al (2009) evaluated the HSRL extinction coefficient profiles and found that the HSRL extinction profiles are within the systematic errors of airborne in situ measurements at visible wavelengths. Derived products include, first, estimates of planetary boundary layer heights which use the vertically resolved profile measurements of aerosol backscatter to derive aerosol mixed-layer heights during the daytime (Scarino et al, 2014).…”
Section: The High Spectral Resolution Lidar (Hsrl-2)mentioning
confidence: 95%
“…Frontiers in Remote Sensing | www.frontiersin.org October 2021 | Volume 2 | Article 706851 Espinosa et al, 2019 W. R.;Puthukkudy et al, 2017;Schuster et al, 2019, etc.). A demonstration of one such retrieval study using measurements of polystyrene (PSL) spheres from Espinosa et al ( 2017) is shown in Figure 7.…”
Section: Laboratory and In Situ Observations Of Aerosol Single Scatte...mentioning
confidence: 99%
“…There are also some efforts to adapt GRASP for processing the observations by the future DPC, Aerosol-UA, HARP2 missions. For example, Figure 17 illustrates the application of the GRASP algorithm for processing AirHARP (airborne Hyper Angular Rainbow Polarimeter) observations made during the NASA ACEPOL 2017 campaign (Puthukkudy et al, 2020a). GRASP retrieved AOD using the AirHARP data is validated using the collocated AERONET and HSRL2 measurements.…”
Section: Satellite and Airborne Passive Observationsmentioning
confidence: 99%
“…The figure also shows an example of data collected during the ACEPOL campaign, its second deployment. The instrument's maiden field campaign was the Lake Michigan Ozone Study (LMOS) in 2017(McBride et al, 2019. For ACEPOL, AirHARP collected data over defined targets, as the processing speed of the onboard data acquisition system precluded continuous data collection.…”
Section: The Airborne Hyper Angular Rainbow Polarimeter (Airharp)mentioning
confidence: 99%
“…For level-2 processing (Fu et al, 2019), the SPEX airborne team has focused on aerosol retrievals, building further on the SRON aerosol retrieval algorithm previously used for POLDER-3 processing (Hasekamp et al, 2011, Lacagnina et al, 20162017) and groundSPEX (van Harten et al, 2014;di Noia et al, 2014). The algorithm has been extended from a bi-modal retrieval scheme to a multi-mode retrieval scheme for an arbitrary number of modes (Fu and Hasekamp, 2018).…”
Section: The Airborne Spectrometer For Planetary Exploration (Spex Aimentioning
confidence: 99%